Improvement of socio-hydrological model to capture the dynamics of pluvial floods: a case study in frequent pluvial flooding areas in Wakayama City, Japan - Komori, Daisuke; Oyatsu, Yuika; Sadidah, Muthiah; Nagami, Kozo (Frontiers in Water, 2025)
In conventional socio-hydrological research, no studies have developed a system dynamics model to capture the dynamics of pluvial floods alone, and the target areas have been large-scale, such as cities and river basins. Thus, the target social community is not single entity but rather multiple, encompassing various communities, including both disaster-stricken and non-disaster-stricken areas. In this study, we developed a system dynamics model to capture the dynamics of pluvial floods alone. We identified frequent pluvial flooding areas using flooding area records since 1993 for 25 years for only targeting disaster-stricken areas on a scale of 400–1,000 m2, and applied the developed model to these areas and verified that social vulnerability (levee effect and adaptation effect) could be explained by residents' flood memory estimated by the model. The adaptation effect, a phenomenon in which the continued memory of flooding enhances a society's ability to cope with flooding and reduces social vulnerability, occurred in both urban areas with public drainage systems and rural areas without public drainage systems. On the other hand, the levee effect, a phenomenon in which the frequency of flooding within the floodplain decreases by installing flood control facilities, the development of floodplain areas is promoted, increasing social vulnerability, and flood control facilities are enhanced to improve further flood control safety, which is a typical phenomenon involving the interaction between human activities and flooding, occurred only in rural areas. It was considered that residents' awareness of the increased flood risk in the area due to changes in land use from rice paddy fields to residential areas was lacking, as they had no prior experience with severe floods. In this study, by simplifying the analysis of disaster-stricken areas (frequent pluvial flooding areas), it was possible to capture the interaction between the simplified social community and flooding more directly, allowing the adaptation and levee effects to be more clearly captured. In future socio-hydrology research, it is essential to consider the scale of the analysis target.